Invigorasi Benih untuk Memperbaiki Perkecambahan Kacang Panjang (Vigna unguiculata Hask. ssp. sesquipedalis) pada Cekaman Salinitas - , Erinnovita; Maryati Sari; Dwi Guntoro (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The objective of this research was to study the influence of invigoration on yard-long bean seed germination under salinity stress. The research was conducted at Seed Science and Technology Laboratory, Department of Agronomy IPB from September to December 2007. Seed of two yard-long bean (Vigna unguiculata Hask. ssp. sesquipedalis) varieties, i.e. 777 and Landung Super, were used to investigate the effects of invigoration treatments, i.e. water soaking, sand priming, sawdust matriconditioning, osmoconditioning with CaCl2, NaCl, KCl and KNO3, under salinity 1.0% NaCl (w/v) stress condition. Sand priming and water soaking treatments significantly enhanced the germination percentage, speed of germination and dry matter of normal seedling under the salinity stress condition. Germination percentage of seed with sand priming was 33.33% higher than tgat of control, and germination percentage of seed with water soaking was 28.66% higher than that of control. The result suggested that sand priming and water soaking were the effective methods to improve yard-long bean seed germination under salinity stress condition. Key words: invigoration, salinity stress, sand priming, water soaking, yard-long bean seed